2018
DOI: 10.1021/acs.jpcb.7b10479
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Mechanical Characteristics of Ionic Liquid Modified MWCNT-SBR Composites: Theoretical Perspectives for the Nanoscale Reinforcement Mechanism

Abstract: Well-dispersed, robust, mechanicaly long-term stable functionalized multiwalled carbon nanotube (f-MWCNT)-styrene butadiene rubber (SBR) nanocomposites were fabricated via a melt mixing route with the assistance of ionic liquid as a dispersing agent. The mechanical properties of f-MWCNT/SBR vulcanizates were compared over a range of loadings, and it was found that the network morphology was highly favorable for mechanical performance with enlarged stiffness. A comparative investigation of composite models foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 29 publications
4
33
0
Order By: Relevance
“…Details regarding the functionalization and characterization of ionic liquid modified MWCNT are given in our previous reports. [2,6] All compounding ingredients were of analytical grade. The crosslinking agent used was sulfur supplied by Merck India Ltd, Mumbai, India.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details regarding the functionalization and characterization of ionic liquid modified MWCNT are given in our previous reports. [2,6] All compounding ingredients were of analytical grade. The crosslinking agent used was sulfur supplied by Merck India Ltd, Mumbai, India.…”
Section: Methodsmentioning
confidence: 99%
“…[1] In our previous studies, we have explored the influence of ionic liquid modified MWCNT (f-MWCNT) on the mechanical, electrical, pervaporation, rheological, morphological, and electromagnetic interference shielding characteristics of styrene butadiene rubber (SBR) nanocomposites. [2][3][4][5][6] The influence of reinforcing agents on the solvent diffusion behavior of polymers has got tremendous attention among scientists. [7] Several studies have been reported on the diffusion of solvents through different varieties of polymers including elastomers, thermoplastics, blends, and interpenetrating networks.…”
Section: Introductionmentioning
confidence: 99%
“…Vulcanisation kinetics study shows that cure reaction is an autocatalytic reaction. [1][2][3][4][5][6][7][8][9][10][11][12][13]…”
Section: Vulcanisation Kineticsmentioning
confidence: 99%
“…Rubbers are recognized as strategically important elastic materials and have been extensively applied in many fields . Generally, almost all rubber matrix need to be reinforced with inorganic fillers to fulfill the ultimate practical applications due to their poor mechanical strength . In recent years, driven by the pressure from environmental issues, some industrial wastes and by‐products such as fly ash, marble waste powder, and agricultural waste have been utilized as the alternative of commercial fillers in rubber composites.…”
Section: Introductionmentioning
confidence: 99%